Respuesta :

X= -2.411

Y= -0.0593

Step-by-step explanation:

Step 1:

Let the given equations be

   2X+3Y= -5 ------------- 1

   5X-Y= -12  --------------2

Multiply 3 in equation 2, we get

15X-3Y= -36  -------------3

Step 2:

On adding equation 1 and equation 3 , we get

       2X+3Y= -5

       15X-3Y= -36

       17X = -41

On solving the above equation, X= -2.411

To get Y value substitute X value in equation 1 we will get

     3Y= -5-2(-2.411)

          = -0.178

     Y = (-0.178)/3

      Y= -0.0593